2016
DOI: 10.4238/gmr.15017879
|View full text |Cite
|
Sign up to set email alerts
|

Association between ERCC1 and ERCC2 gene polymorphisms and susceptibility to pancreatic cancer

Abstract: ABSTRACT. We conducted a study to investigate the association between ERCC1 (rs3212986) and ERCC2 (rs13181) gene polymorphisms and the risk of pancreatic cancer in a Chinese population. A total of 217 pancreatic cancer patients and 244 control subjects were recruited from the Nuclear Industry 215 Hospital of Shaanxi Province between February 2013 and December 2014. Genomic DNA was extracted from peripheral blood samples using a TIANamp Blood DNA Kit (Tiangen, Beijing, China) according to the manufacturer's ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
3
13
1
Order By: Relevance
“…It is not difficult to infer that the children with CT + TT had a reduced ability to repair nucleotide excision; therefore, they had a lower ability to repair PD-induced damage, were more sensitive to PDs, and exhibited better chemotherapy results. The above inference is consistent with the reports of other studies both in and outside China [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is not difficult to infer that the children with CT + TT had a reduced ability to repair nucleotide excision; therefore, they had a lower ability to repair PD-induced damage, were more sensitive to PDs, and exhibited better chemotherapy results. The above inference is consistent with the reports of other studies both in and outside China [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with the T allele may also be more sensitive to PDs [31,32]. Globally, many studies in non-small cell lung cancer [8], ovarian cancer [9], gastric cancer [10], esophageal cancer [11], pancreatic cancer [12], and colorectal cancer [13] have shown patients with the CT or TT genotypes in ERCC1 C118T mutation to be more sensitive to PDs when compared to patients with the CC genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies which focus on the relationship between this SNP and pancreatic cancer [ 11 – 18 ]. Jiao et al (2007), Hocevar et al (2014), Ying et al (2015) and He et al (2016) did not observe any significant association between rs13181 and the risk of pancreatic cancer [ 11 14 ]. However, McWilliams et al (2008), Zhao et al (2015), Yan et al (2016) and Sileng et al (2016) suggested that this polymorphism was associated with an increased susceptibility to pancreatic cancer [ 15 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted using the TIANamp genomic DNA Kit purchased from TIANGEN BIOTECH CO., LTD (Beijing) [ 21 ], according to the manufacturer’s instructions, and was stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%